Rights Share Issue Practice in Nepal - Pathak, Hari Prasad; Giri, Dhanesh (Journal of Nepalese Business Studies, 2009)
The study is focused on practice of rights offering in Nepal and its impact on share price movement. This study covers two interrelated aspects: (a) Characteristics of rights offering of listed companies and (b) Share price movement associated with rights offering. Nepal Finance and Saving Company Ltd. started the practice of rights share in Nepal by issuing right share for the first time in 1st December 1995. In this study, the rights share issue practice and impact of rights offering on market price of share have been analyzed by taking five rights issuing companies as sample. The findings of the study are not consistent with the theory of rights offering. Key Words: Rights share, share price movement, share price index (NEPSE index) The Journal of Nepalese Business Studies Vol. V, No. 1, 2008, December Page: 93-100